Economic Development of Fruit and Vegetable Industry of Kazakhstan - WEI, Peng; UMIRZAKOV, Samazhan Y.; KENZHALINA, Zhanna Sh. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).37, 2019)
The relevance and significance of the research lie in the fact that the fruit and vegetable industry belongs to the agro-industrial sector. The agro-industrial sector is an important industry for the national economy of Kazakhstan region, as it determines the country's food security. The method of quantitative and qualitative analysis, forecasting, and the method of comparative analysis were chosen as the scientific research methods. Following from the study, based on the analysis of the dynamic range of indicators affecting the volume of the industry, we highlighted the problems of its development. The analysis highlighted the factors that may affect the development of the industry. The approach proposed in the article presents ways to overcome existing problems and growth in the industry within the framework of import substitution policies and food security in the region. This article may be of interest to government agencies in drawing up the strategy for the development of the agro-industrial complex, for managers of enterprises, as well as for higher educational institutions engaged in the training of specialists in the field of food industry and economists.